Research methods of V/F control for matrix converter use direct space vector modulation - Bogdan Vasilev; Le Van Tung (Institute of Advanced Engineering and Science, 2019)
Matrix converter (MC) is direct AC to AC converter built on bidirectional switches with more outstanding advantages compared to the indirect AC - DC-AC converter such as power exchange in two directions, allowing regenerative braking performance amount returned grid. However, the modulation method for Matrix converter has the disadvantage of low voltage transmission ratio, current at the input and output current, the voltage of converter has many high-order harmonic components. The paper presents the technique of directly modulating the space vector which will improve the quality of matrix converter such as input and output currents with sine form, power factor input is nearly 1 and can be adjusted. Also, build V/F control method for matrix converter to control three-phase alternating current induction motors. Research results are tested by Matlab & Simulink software.